Daya Terima dan Kandungan Zat Gizi Minuman Sirup dari Limbah Kulit Buah Nanas dan Kulit Buah Jeruk - Rahma, Tria Mareta; Nazarena, Yunita; Yulianto, Yulianto (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Anemia is a nutritional problem that often occurs in teenagers. Anemia is a condition where the hemoglobin (Hb) concentration is below normal values, characterized by lethargy, lightheadedness, dizziness and pale skin, which can cause a decrease in school activity and performance due to lack of concentration. Vitamin C (ascorbic acid) is a nutrient that acts as an effective antioxidant or overcomes free radicals which can damage cells or tissues, including protecting the lens from oxidative damage caused by radiation. Method: This research is an experimental study with a complete randomized design of non-factorial experiments that are used homogeneously or there are no other factors that influence responses outside the factors studied. Then continue with organoleptic tests and laboratory tests of the best syrup formula nutrients. Results: Based on the results of this study, the receipt of color was most preferred by panelists in formula 3, 53.3%, the receipt of aroma was most preferred by panelists in formula 3, 53.3%, the receipt of taste was most preferred by panelists in formula 3, 50.0%, the receipt of texture was most preferred by panelists in formula 3, 50.0%. The best formula after an organoleptic test is F3 treatment. And the results of the proximate analysis of F3 treatment per 100 ml are 100.74 Kcal, protein <0.04 grams, fat <0.02 grams, carbohydrates 25.185 grams, water content 74.26%, ash content 0.555%, and vitamin C 4.145%. Conclusion: The best formula for syrup from pineapple peel and orange peel waste is F3 treatment.